2009
DOI: 10.1371/journal.ppat.1000570
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionarily Conserved Herpesviral Protein Interaction Networks

Abstract: Herpesviruses constitute a family of large DNA viruses widely spread in vertebrates and causing a variety of different diseases. They possess dsDNA genomes ranging from 120 to 240 kbp encoding between 70 to 170 open reading frames. We previously reported the protein interaction networks of two herpesviruses, varicella-zoster virus (VZV) and Kaposi's sarcoma-associated herpesvirus (KSHV). In this study, we systematically tested three additional herpesvirus species, herpes simplex virus 1 (HSV-1), murine cytomeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
211
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(222 citation statements)
references
References 58 publications
8
211
1
2
Order By: Relevance
“…Given two CGOPs, u, j(u) and v, j(v), there is an interaction between u and v. If there is an interaction between j(u) and j(v), Fig. 8 Phylogenetic trees reconstructed using three different methods a Phylogenetic tree reconstructed using the method of Fossum et al [20] b Phylogenetic tree reconstructed using the method of Natasa et al [8] c Phylogenetic tree reconstructed using HGA-2N The three trees show the same phylogenetic relationships these two interactions are conserved interactions. If there is no interaction between j(u) and j(v), a potential interaction can be predicted between j(u) and j(v).…”
Section: Ppi Analysesmentioning
confidence: 99%
“…Given two CGOPs, u, j(u) and v, j(v), there is an interaction between u and v. If there is an interaction between j(u) and j(v), Fig. 8 Phylogenetic trees reconstructed using three different methods a Phylogenetic tree reconstructed using the method of Fossum et al [20] b Phylogenetic tree reconstructed using the method of Natasa et al [8] c Phylogenetic tree reconstructed using HGA-2N The three trees show the same phylogenetic relationships these two interactions are conserved interactions. If there is no interaction between j(u) and j(v), a potential interaction can be predicted between j(u) and j(v).…”
Section: Ppi Analysesmentioning
confidence: 99%
“…Une partie de ces défenses immunitaires est innée et s'exprime très précocement au sein des cellules de l'organisme en réponse à l'activation de sentinelles moléculaires. C'est le cas des récepteurs membranaires TLR (récepteurs Toll-like) et des senseurs intracellulaires l'interactome viral par la technologie du double hybride en levure (Y2H : yeast two-hybrid) réalisées à l'échelle de plusieurs virus entiers dont celui de l'hépatite C [9], du SARS (severe acute respiratory syndrome) [10] et de plusieurs herpèsvirus [11,12]. Des travaux récents ont également été entrepris pour explorer sans a priori l'interactome virus-hôte, dont celui de l'EBV (Epstein Barr [13], du virus de l'hépatite C [14] et du virus de la vaccine [15].…”
Section: Génomique Virale Recherche Des Composantes Du Systèmeunclassified
“…Further, on studying three additional herpesvirus species, herpes simplex virus 1 (HSV-1), murine cytomegalovirus and Epstein-Barr virus, a core set of highly conserved protein interactions were identified. Interactions are conserved between orthologous proteins despite low sequence similarity, suggesting that function may be more conserved than the sequence [7]. While another study revealed, the inducible form of cyclooxygenase is COX-2 expression, whose tight regulation is necessary for controlling eicosanoid production in atherosclerosis and other inflammatory syndromes.…”
Section: Protein Interactions and Diseasesmentioning
confidence: 99%